The tactics of psychotherapeutic support of patients with psychoendocrine syndrome caused by hypothyroidism - Ishchuk, V. (Journal of Education, Health and Sport, 2019)
In order to form of nosogenic-differentiated system of psychotherapeutic support for patients with psychoendocrine syndrome on the background of hypothyroidism, at the Ukrainian Scientific and Practical Center for Endocrine Surgery, Transplantation of Endocrine Organs and Tissues of the Ministry of Health of Ukraine, 100 patients with hypothyroidism were examined. Within the framework of the psychodiagnostic study, which included, in particular, a structured psychodiagnostic interview aimed at identifying and systematizing of nosogenic predictors of psychotraumatisation, the chronopathology and introspectively-vital groups were identified. Based on the analysis of variants of a dynamic stereotype, the interpretation of the nature of the influence of nosogenic predictors of psychotraumatic disorders in a psychosomatic perspective was performed.Based on the analysis of dynamic stereotype variants, the interpretation of the nature of the influence of nosogenic predictors of nosogenic-stress in psychosomatic perspective and developed principles of psychotherapeutic support of patients with PES оn the background of hypothyroidism were developed.